Approbation of the express penetration method for assessing the strength of sedimentary cohesive rocks - Vynnykov, Yuriy; Bondar , Andrii; Liashenko , Anna; Novokhatniy , Valeriy; Rybalko , Мaryna (Academic journal Industrial Machine Building Civil Engineering, 2023)
The advantages of express methods of penetration and probing for evaluating the mechanical parameters of cohesive sedimentary rocks over traditional methods of testing them in single-plane displacement devices, odometers, and stabilometers are analyzed, such as: complete independence from the applied force and cone immersion depth; simplicity and reliability of the equipment; high reliability of results, etc. The methodology and results of 185 sets of penetration-shear tests of various clay rocks, from sandy loams to clays, are presented. Their results were used to determine the strength indicators of cohesive rocks (angle of internal friction and specific adhesion). Through statistical processing of experimental data, it was confirmed that for the water-saturated state of clay rocks there is an almost functional relationship between the penetration index and the porosity coefficient.
Keywords: well; sedimentary cohesive rock; strength; express method of penetration; specific penetration resistance; uniplanar displacement; internal friction angle; specific adhesion; the equation of interrelation